Penentuan Tingkat Pemahaman Mahasiswa dalam Matakuliah Kelas Daring dengan Algoritma C4.5 (Studi Kasus: Mahasiswa/i FTI Angkatan 2019) - Tarigan, Aldy Alvharo; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The purpose of this study was to classify using the C4.5 algorithm to determine student understanding of online lectures at the SWCU Information Technology Faculty. In carrying out lecture activities where students must conduct online lectures, students are expected to be able to understand all the material provided. Many things affect student understanding in digesting online lecture material. The data was taken from the questionnaire results from the 2019 SWCU Information Technology Faculty student. The five attributes used were the learning atmosphere, learning tools, communication, teaching methods, and networking. The research method used is the C4.5 algorithm which builds a decision tree using RapidMiner software. Based on the results of the study, there were 27 rules with 18 rules understood rules . In the case of students' level of understanding in online classes, the accuracy rate reaches 70%, which means that students quite understand the courses presented online.